LEGAL PROCESSES AS THE BASIS OF THE MODERN LEGAL INTEGRATION - Aiupova Зауре Каримовна; Zaure Karimovna Кусаинов (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2015)
In this article the theoretical bases of the legal processes in modern Euroasian economic space, and also their role in improvement and development of legal integration of economy of the Republic of Kazakhstan in the Euroasian Union are investigated. Questions of internationalization of the legislation, legal annihilation, legal expansion, reception of the right, unification (assimilation) of the right, emulation or imitation, penetration and harmonization are considered. Opinions of authoritative scientists-jurists of the states of the CIS on the studied questions are given.